Peta Konsep Mahasiswa dalam Penelitian Sastra: Studi Kasus Tahun Kademik 2013 dan 2014 - Hazairin Eko Prasetyo; Afria Dian Prastanti (Universitas Sarjanawiyata Tamansiswa, 2017)
A preliminary observation on the studentsâ€™ term papers of the English language education department of Sarjanawiyata Tamansiswa University showed that, in terms of using of concept maps, some were completed with ones and the others were not. Therefore, it was interesting to do a research on this issue. However, due to time limitation, this study focused on the term papers with concept maps and the objective of the research was to find out how students developed their concept maps. The research method was a mixed-method between quantitative and qualitative techniques. The objects of the research were the term papers on literature accomplished during the academic year 2013/2014. The quantitative technique was applied in classifying the objects according to the proportion of interest, while the qualitative technique was used to analyze the findings descriptively. The results of the research showed that 16.39% of 137 students writing term papers during the academic year analyzed literary works 91.30% Â of which used concept maps. The concept maps could be classified into two groups: comprehensive and partial.